Enhancement of Case Hardness in AISI1025 Steel at Low Voltage Micro Arcing in a Liquid Solution - Dr. Shrikisan Parihar, Dr. Sanjay Purkar, Dr. Dharmendra Kumar Dubey (International Journal of Advanced Science and Technology, 2020)
Micro arcing developed at an electrode having smaller surface area as compared with that of the other electrode of an electrolytic cell when the cell was supplied DC voltage of around 61volts. AISI1025 steel specimens of 20mm diameter and 50 mm length were treated in an electrolytic cell with an aqueous solution of 100ml glycerin and 100gmNH4Cl. Voltage applied to the cell was gradually raised from 0 to 110 Volts. Current-voltage data was acquired using data aquision card. Temperature measurement was done using chromel_alumel thermocouple. Hardness measurements were done using Vickers hardness tester. Microstructural characterization and elemental analysis was done by optical and SEM techniques